2020
DOI: 10.1136/bmjdrc-2020-001275
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus among adults with tuberculosis in the USA, 2010–2017

Abstract: IntroductionTo describe diabetes trends among adults with incident tuberculosis (TB) disease and examine diabetes-associated TB characteristics and patient outcomes in the USA.Research design and methodsWe examined all 71 855 persons aged ≥20 years with incident TB disease reported to the National Tuberculosis Surveillance System during 2010–2017. We performed multivariable logistic regression, comparing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Corroborating such findings, studies conducted in the United States (37) and in Spain (38) have also shown an increase in comorbidity prevalence over time. Although the number of TB cases has been decreasing in countries like the United States, the prevalence of DM as comorbidity reported among adults with TB has steadily grown due to the high DM prevalence (37) .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Corroborating such findings, studies conducted in the United States (37) and in Spain (38) have also shown an increase in comorbidity prevalence over time. Although the number of TB cases has been decreasing in countries like the United States, the prevalence of DM as comorbidity reported among adults with TB has steadily grown due to the high DM prevalence (37) .…”
Section: Discussionmentioning
confidence: 77%
“…Besides, alterations in lung function and mucociliary clearance in older adults, associated with the immunological vulnerability caused by DM, favor the development of TB (14) . DM and the physiological aging process synergistically reduce interferon-gamma levels, impairing cell-mediated immunity that contributes to the activation of long-standing latent TB (37) .…”
Section: Discussionmentioning
confidence: 99%
“…All patients aged ≥45 years old and all younger patients with risk factors for diabetes should be screened for diabetes at the beginning of TB treatment. 11 Diabetes may affect the natural history of TB in many ways, resulting in potentially increased risks of TB infection, clearly much higher chances of TB disease, and poorer TB treatment outcomes, especially mortality both during and after the end of treatment. 12 There are various challenges and substantial evidence with gaps regarding the management of TBLN with a pre-existing condition such as HIV or diabetes and the management of TBLN only.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for the combined group were: (1) diagnosed with TB according to guidelines for the diagnosis and treatment of TB published by the Chinese Medical Association, 11 including pathological tissue biopsy and etiological examination; (2) diagnosed with type 2 diabetes according to guidelines for the prevention and treatment of type 2 diabetes in China; 12 (3) positive acid-fast staining of a sputum smear; (4)…”
Section: Study Patientsmentioning
confidence: 99%
“…3 Compared with patients with TB alone, patients with TB and diabetes have a worse prognosis and a higher mortality rate during anti-TB treatment. 4 Therefore, a reliable diagnostic method is of great clinical importance for defining the treatment plan and improving the survival rate of patients with TB.…”
Section: Introductionmentioning
confidence: 99%